A República de Platão: relação entre os livros I, II, III, IV e VIII - Leite, José Assunção Fernandes (2009)
One of the criticisms that have been made to the Book I of the Republic is the fact that it is disconnected from the remaining of the work, since there is an aporia at the end of the dialogue, a characteristic of dialogues from Plato s youth, also known as Socratic for dealing with questions deemed as ethical. The model of dialogue written by Plato in his youth, and its similarities with the Book I have lead some commentators to believe that this book may precede the others, and even be out of the context of the work. Being aware of the complexity of this piece of work from Plato, we proceeded to verify whether in fact this first book does not belong with the others. To this end it was necessary to choose a proper approach, since depending on one s purpose different paths can be followed in the Republic. We collected the theses of the characters from Book I and II to check whether or not the aforementioned philosopher will abandon the ideas presented by Cephalus, Polemarchus, Thrasymachus, Glaucus and Adeimantus. Given their theses, we noticed firstly the methodological differences in the dialogues between the characters. Secondly, we detected a relationship between the three theses and the three sectors, and between the three powers of the soul and the myth of the races in the Book III. Finally, given the just city and its fundaments, we studied the relationship between the character s theses and the constitution models regarded as decadent in the Book VIII, analysing whether such theses are present or not, partially or integrally. In this process of analysing the constitutions, we also paid attention to the education adopted in each one of the pólis models. Our reflection in the present work consisted in demonstrating that the Book I of the Republic is not disconnected from the remaining of the work, since the earlier theses reappear in some form in the Book VIII